Pragmatics and Philosophy. Connections and Ramifications - Capone, Alessandro; SpringerLink (Online service) (Cham : Springer International Publishing : Imprint: Springer, 2019)
This book shows how pragmatics and philosophy are interconnected, and explores the consequences and ramifications of this innovative idea, especially in addressing and solving the problem of breaking Grice's circle. The author applies philosophy in order to get to a better understanding of pragmatics, and pragmatics in order to get a better understanding of philosophy. The book starts with a chapter on the non-cancellability of explicatures and the role that this idea plays in the resolution of Grice's circle, and proceeds with the discussion of other topics in which explicatures or cancellability play an important and decisive role. While the reader proceeds in the reading of this book, they accumulate notions and pieces of knowledge which will be of invaluable use when arriving at the chapter on conversational presuppositions (and related chapters), where the author expresses his most radical views: namely that (potential) presuppositions are indeed cancellable, contrary to what many believe.
Chapter 1. Introduction -- Chapter 2. On a theory-internal problem in the semantics/pragmatics debate: how to resolve Grice's circle -- Chapter 3. On the nature of pragmatic increments at the truth-conditional level -- Chapter 4. On the tension between semantics and pragmatics -- Chapter 5. The pragmatics of referential and attributive expressions -- Chapter 6. The clitic 'lo' in Italian, propositional attitudes and presuppositions -- Chapter 7. Quotation with and without quotation marks -- Chapter 8. Knowing how and the semantics/pragmatics debate -- Chapter 9. Indirect reports and societal pragmatics -- Chapter 10. What happens when we report grammatical, lexical and morphological errors? -- Chapter 11. Maier on the alleged transparency of mixed quotation -- Chapter 12. Conversational presuppositions. Presupposition as defeasible (and non-defeasible) inference -- Chapter 13. Presuppositions in indirect reporting.
Keywords: Pragmatics; Language and languages -- Philosophy; Semiotics; Pragmatics; Philosophy of Language; Semiotics